Principales enfermedades en el cultivo de melón (Cucumis melo L.) en el Ecuador - Prado Vargas, Byron Ariel (2022)
Diseases are one of the limiting factors in melon crop production, decreasing yields or affecting the pleasantness of the final product. Diseases can be a consequence of inadequate agronomic management within the melon crop and the most critical, in decreasing order according to the economic damage they cause are: fungi, bacteria and viruses. The management of the main diseases in the melon crop should be considered from planting for seedling production until harvest, so that diseases can be counteracted, or in case they arise, to prevent their spread. The epidemiological understanding of diseases affecting melon allows us to apply efficient control techniques. The information obtained was analyzed, synthesized and summarized to provide the reader with information on the main diseases affecting melon (Cucumis melo L.) in Ecuador. In the perspective on the main diseases in the melon crop (Cucumis melo L.) in Ecuador, the following conclusions were reached: The most important diseases in papaya crop are: anthracnose (Colletotrichum lagenarium), leaf spot (Alternaria cucumerina), Fusarium wilt (Fusarium oxyporum), downy mildew (Pseudonospora cubensis), angular leaf spot (Pseudomonas syringae), bacterial wilt (Erwinia tracheiphila) and Cucumber Mosaic Virus (CMV - Cucumber Mosaic Virus). For the management of the main fungal, bacterial and viral diseases, the use of tolerant varieties is recommended. Avoid situations that promote succulent growth, such as immoderate fertilization. In addition, the use of preventive and curative fungicides could be another important advice to avoid serious damage to the crop.